The ethic's privatization in Brazil: positioning of Petrobras in the Youtube channel - Cabral, Raquel [UNESP]; Andrelo, Roseane [UNESP]; Granato, Mariany Schievano [UNESP] (Univ Malaga, Inst Investigacion Relaciones Publicas, 2018)
This article investigates the construction of content related to ethics, in digital technologies of communication and information, centralized in the Youtube channel of the Brazilian state-owned oil company Petrobras, after the denunciations of public money diversion verified by the Federal Police through the operation titled Car wash. We attempted to analyze the types of connections generated from this content: associative or emergent (Recuero, 2012). The problematic situation lies in how companies deal with the issue of ethics in postmodernity, especially when there are cases of proven corruption and need to restore public confidence. It is presumed that these companies have begun a privatization movement of ethics, launching departments of ethical conduct to prove integrity, especially in the face of public opinion, as well as using biased speeches, as demonstrated in the content analysis in four videos made available by Petrobras in your Youtube channel. For the theoretical foundation, concepts such as postmodernity, public information, public relations, ethics and social capital are approached
Keywords: ethics; Petrobras; digital technologies of information and communication; social capital; public relations